Sistem Pendukung Keputusan Penilaian Guru Teladan Smk Al-Hikmah Sumobito Berbasis Website Menggunakan Metode Smart - Zulfa, Abidah; Zein Vitadiar, Tanhella (Inovate, 2023)
Al Hikmah Vocational High School is one of the equivalent vocational / high school level educations that stands in Sumobito. In this study, it was taken to improve the quality and quality of the students of SMK Al Hikmah Sumobito. Especially to teachers and staff who work at SMK Al Hikmah Sumobito, in this study it can also improve the quality for teachers who get the best rankings who will get promotions and appreciation from the principal of SMK Al Hikmah Sumobito. Which aims to design and build a Website-Based Decision Support System for Exemplary Teacher Assessment at Al-Hikmah Sumobito High School and develop better human resources. The results of the design and development of this system can be used as information material for the next practitioner in making or developing a decision support system for selecting the best teacher using the website-based SMART method. Keywords: Decision Support System, SMART, Examplari Teacher